The polyphasic chlorophyll a fluorescence rise measured under high intensity of exciting light - Lazár, Dušan (Functional plant biology, 2006)
Chlorophyll a fluorescence rise caused by illumination of photosynthetic samples by high intensity of exciting light, the O-J-I-P (O-I1-I2-P) transient, is reviewed here. First, basic information about chlorophyll a fluorescence is given, followed by a description of instrumental set-ups, nomenclature of the transient, and samples used for the measurements. The review mainly focuses on the explanation of particular steps of the transient based on experimental and theoretical results, published since a last review on chlorophyll a fluorescence induction [Lazár D (1999) Biochimica et Biophysica Acta 1412, 1-28]. In addition to 'old' concepts (e.g. changes in redox states of electron acceptors of photosystem II (PSII), effect of the donor side of PSII, fluorescence quenching by oxidised plastoquinone pool), 'new' approaches (e.g. electric voltage across thylakoid membranes, electron transport through the inactive branch in PSII, recombinations between PSII electron acceptors and donors, electron transport reactions after PSII, light gradient within the sample) are reviewed. The K-step, usually detected after a high-temperature stress, and other steps appearing in the transient (the H and G steps) are also discussed. Finally, some applications of the transient are also mentioned.